Sailing the Archipelago in a boat of rhymes; Pantun in the Malay world - Salleh, Muhammad Haji (Wacana, Journal of the Humanities of Indonesia, 2011)
The extremely popular poetic form from Insular Southeast Asia, the pantun, travelled from its unknown source throughout the Malay Archipelago, first in Malay, then in the languages of Southeast Asia. In the ports and states where they were received, local colour, other idiosyncrasies, references, and linguistic characteristics have been added, and in fact, special forms with special names developed. This basic form is known, composed, and loved in at least 40 dialects of Malay, and 35 non-Malay languages, in the Peninsula and many of the islands of Malaysia and Indonesia. It spread through trade routes, ports, and also via diasporas and colonial economic projects which caused numerous peoples to move, who in turn brought the pantun along with them. It is now the most dynamic single literary form and has the longest history.